2013
DOI: 10.1108/03699421311301142
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of poly(vinyl alcohol) coating mixed with anthocyanin dye extracted from roselle flower with different nitrate salt

Abstract: Purpose -The purpose of this paper is to develop a new water-based coating system composed of poly(vinyl alcohol) and anthocyanin colourant extracted from Hibiscus sabdariffa L. and to characterise the system. Design/methodology/approach -Anthocyanin from Hibiscus sabdariffa L. (roselle) calyxes was extracted by using distilled water and filtered to remove insoluble particle. Salts introduced into the extract were 5wt percent calcium nitrate, 5wt percent magnesium nitrate, and 5wt percent zinc nitrate. The sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…This increment was due to the ionic crosslinking, which restricted the free motion of the PVA chains. Similar results were reported by Lee et al 52 for PVA and nitrate salt mixture. The melting points of 5M‐PVA and 10M‐PVA films were determined to be 188 and 181°C, respectively.…”
Section: Resultssupporting
confidence: 92%
“…This increment was due to the ionic crosslinking, which restricted the free motion of the PVA chains. Similar results were reported by Lee et al 52 for PVA and nitrate salt mixture. The melting points of 5M‐PVA and 10M‐PVA films were determined to be 188 and 181°C, respectively.…”
Section: Resultssupporting
confidence: 92%
“…Kljajević et al [27] observed the appearance of nepheline in the research by analyzing thermally treated metakaolin-based geopolymers without the addition of organic matter. One part of PVA most likely acts with reactive silicon from the mixture and can be defined as filler that strengthens the geopolymer matrix [28]. The addition of PVA to the basic reaction mixture during the synthesis of geopolymers most likely affects the migration of Na, Al, and Si in the silicate matrix where their precipitation and reorganization from dissolved phases occurs [25].…”
Section: Xrd Analysis Of Hybrid Geopolymersmentioning
confidence: 99%
“…The weak absorption peak observed at 1327 cm −1 is due to the C-OH bending vibration. The peak at 1732 cm −1 is due to the presence of carbonyl (C=O) stretching of the non-hydrolysed residual vinyl acetate group of PVA [32]. The FTIR spectra of PSC composite films revealed different features.…”
Section: Fourier Transform Infrared (Ftir) Spectroscopymentioning
confidence: 99%